2017
DOI: 10.15537/smj.2017.9.18532
|View full text |Cite
|
Sign up to set email alerts
|

Factors influencing the psychology and quality of life in lung cancer patients

Abstract: Objectives:To determine the factors closely correlated with the unhealthy psychological status of patients with lung cancer and to ascertain whether the unhealthy psychology adversely affects their quality-of-life (QOL).Methods:Patients newly diagnosed with lung cancer between May 2013 and December 2015 in the Department of Thoracic Surgery, Tianjin 4th Centre Hospital, Tianjin, China were enrolled in this cross-sectional study. Patients were asked to complete the Symptom Checklist 90 (SCL-90) and Quality of L… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
16
0
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(19 citation statements)
references
References 16 publications
1
16
0
2
Order By: Relevance
“…The secondary endpoints were progression‐free survival (PFS), overall survival (OS), and quality of life evaluated by QLQ‐C30 questionnaire . The QLQ‐C30 evaluates self‐assessed health status and social, physical, and emotional functioning, based on 30 items, grouped into five functional scales (physical functioning, role functioning, emotional functioning, cognitive functioning, and social functioning), three symptom scales (fatigue, nausea and vomiting, and pain), and six single questions (evaluating the severities of dyspnea, insomnia, appetite loss, constipation, diarrhea, and financial difficulties).…”
Section: Methodsmentioning
confidence: 99%
“…The secondary endpoints were progression‐free survival (PFS), overall survival (OS), and quality of life evaluated by QLQ‐C30 questionnaire . The QLQ‐C30 evaluates self‐assessed health status and social, physical, and emotional functioning, based on 30 items, grouped into five functional scales (physical functioning, role functioning, emotional functioning, cognitive functioning, and social functioning), three symptom scales (fatigue, nausea and vomiting, and pain), and six single questions (evaluating the severities of dyspnea, insomnia, appetite loss, constipation, diarrhea, and financial difficulties).…”
Section: Methodsmentioning
confidence: 99%
“…At the same time, due to the variety of cases admitted in different departments, the key points and difficulties in the treatment of different diseases are different, so focusing on the key links in the treatment and nursing process to promote the health care team as the core of the intervention is the key to ensuring the quality of clinical treatment and nursing care. The results of a recent study by Wang et al[ 7 ] showed that the pain experienced by lung cancer patients after radical resection was significantly reduced, and their hospital stay was significantly reduced. The study confirmed that in addition to negative emotions being alleviated, serum tumor markers, such as cancer antigen 125 and carcinoembryonic antigen, were also significantly decreased.…”
Section: Discussionmentioning
confidence: 99%
“…Surgery and chemotherapy are essential measures for the clinical treatment of lung cancer[ 4 ]. However, the disease itself can lead to severe anxiety and mood swings, an enormous physical and mental burden, and surgery and chemotherapy can cause trauma, that may aggravate the negative feeling of patients[ 5 , 6 ], which is not conducive to the treatment of disease[ 7 , 8 ]. Therefore, positive nursing interventions during the treatment of lung cancer patients are most effective[ 9 , 10 ].…”
Section: Introductionmentioning
confidence: 99%
“…Zvýšení kvality života onkologických pacientů je hojně diskutovaným, celospolečenským tématem. To reflektuje značné množství studií zabývajících se problematikou (Aaronson et al, 1993;Kim & Kim, 2017;Litwin et al, 1995;Spitzer et al, 1981;Thongprasert, 1998;Wang, Hao, & Zhang, 2017).…”
Section: úVodunclassified
“…Jako nejdůležitější uváděli věk, úroveň vzdělání, zaměstnání, příjem, kouření, dobu od zjištění diagnózy, subjektivní hodnocení zdraví, míru stresu, depresi či představování sebevraždy. K závěru, že kvalitu života u pacientů s onkologickým onemocněním ovlivňuje celá řada faktorů, dospěli i Wang et al (2017). Na základě výzkumu mezi respondenty s rakovinou plic dochází autoři k výsledkům, že mezi klíčové faktory patří pohlaví, věk, historie chirurgických zákroků či zaměstnání.…”
Section: Diskuseunclassified